ANTHROPOMETRIC INDICATORS OF GROWTH AND NUTRITIONAL STATUS IN THREE -YEAR-OLD MACEDONIAN CHILDREN - Trpkovska, Biljana; Zafirova, Biljana; Matveeva, Niki; Stojanoska, Biljana Bojadzieva; Chadikovska, Elizabeta; Kordoska, Jovana; Paunkoska, Anamarija; Jovanovska, Viktorija; Telenta, Julija; Georgieva, Elena (Journal of Morphological Sciences; Vol 9 No 1 (2026): JMS, 2026)
Growth monitoring and promotion of optional growth are essential components of primary health care for children. Serial measurements of weight, height/length, for all children, and measurements of circular and transversal parameters compared with growth of a large sample population help to confirm a child’s healthy growth and development. It also allows early identification of potential nutritional or health problems and enables prompt action before a child’s health is seriously compromised. The aim of the study is evaluation of sex-specific differences in anthropometrical parameters as indicators of growth. The study included 200 healthy 3 years old preschool children from Macedonian nationality. Thirteen anthropometric parameters were measured, defining longitudinal, circular and transversal dimensionality of the skeleton using standard technique and instruments for measurement. The following indices were selected and calculated: weight-for –age; height-for-age and BMI. Skin –folds (triceps, scapula and thigh) were also measured. Sex-specific differences for almost all anthropometric parameters were detected, but they were not significant. Girls showed higher values than boys regarding height, weight but for BMI were significant in boys. Values at the 50 th percentile in girls were 16.8 kg for BW, 102 cm for BH and 16.5 kg/m². The values of these parameters in boys were 18 kg for BW, 96.93 cm for BH and 17.5 for kg/m² for BMI. The values for skin fold for triceps were higher in girls (13.1 ± 3.5) instead of boys (12.2 ± 3.3). The results obtained can be used for criteria for assessment and detecting deviations in growth and nutritional status in preschool children. Keywords: anthropometry, growth, nutritional status, preschool children.